1995
DOI: 10.1016/0257-8972(95)08356-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrogen during plasma beam deposition of amorphous thin films

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers)Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…[20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22], by pulsed laser ablation of graphite [19], direct ion beam deposition [23], plasma beam deposition [24], mass-selected ion beam deposition [25,26], electron-cyclotronresonance plasma chemical vapor deposition (ECR plasma CVD) [27], radio-frequency-CVD [11], and by filtered cathodic arc plasma deposition [6,16,20,21]. Research over the last years has identified filtered cathodic arc deposition as one of the promising techniques for hard carbon films thinner than 5 nm [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] There are large variations even within each class of materials, depending on the method and parameters of deposition. Diamond-like carbon films can be synthesized by argon sputter deposition using a graphite target [12,22], by pulsed laser ablation of graphite [19], direct ion beam deposition [23], plasma beam deposition [24], mass-selected ion beam deposition [25,26], electron-cyclotronresonance plasma chemical vapor deposition (ECR plasma CVD) [27], radio-frequency-CVD [11], and by filtered cathodic arc plasma deposition [6,16,20,21]. Research over the last years has identified filtered cathodic arc deposition as one of the promising techniques for hard carbon films thinner than 5 nm [28,29].…”
Section: Introductionmentioning
confidence: 99%